1994
DOI: 10.3109/00498259409043270
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a series of natural flavonoids on free radical generating systems and oxidative stress

Abstract: 1. A series of flavonoids isolated from Indian medicinal plants: kaempferol-3-O-galactoside, hispidulin, nepetin, scutellarein, scutellarein-7-O-glucuronide, hibifolin and morelloflavone were studied for their activity as inhibitors of microsomal lipid peroxidation and scavengers of oxygen free radicals in vitro as well as in a model of xenobiotic toxicity in mouse. 2. All compounds inhibited lipid peroxidation in vitro. The most potent compounds were nepetin (non-enzymic lipid peroxidation) and morelloflavone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
105
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(108 citation statements)
references
References 35 publications
2
105
0
1
Order By: Relevance
“…The activity of morelloflavone (1) as an antiinflammatory (Gil et al, 1997;Castardo et al, 2008) and antioxidant (Sanz et al, 1994;Deachathai et al, 2005;Hutadilok-Towatana et al, 2007) are well-documented; it has also been found to be a potent tyrosinase inhibitor (Masuda et al, 2005), anti-HIV-1 (Lin et al, 1997), and anti-bacterial (Verdi et al, 2004) agent, and to have antimalarial (Ngouamegne et al, 2008) and analgesic (Luzzi et al, 1997) properties. Isojacareubin (5) is known for its activity as an anticoagulant (Wu et al, 1998), and 6-deoxyisojacareubin (6) for its antifungal (Morel et al, 2002) and antibacterial (Kuete et al, 2007) properties, while sargaol (4) shows marked activity as an antioxidant (Nahas et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…The activity of morelloflavone (1) as an antiinflammatory (Gil et al, 1997;Castardo et al, 2008) and antioxidant (Sanz et al, 1994;Deachathai et al, 2005;Hutadilok-Towatana et al, 2007) are well-documented; it has also been found to be a potent tyrosinase inhibitor (Masuda et al, 2005), anti-HIV-1 (Lin et al, 1997), and anti-bacterial (Verdi et al, 2004) agent, and to have antimalarial (Ngouamegne et al, 2008) and analgesic (Luzzi et al, 1997) properties. Isojacareubin (5) is known for its activity as an anticoagulant (Wu et al, 1998), and 6-deoxyisojacareubin (6) for its antifungal (Morel et al, 2002) and antibacterial (Kuete et al, 2007) properties, while sargaol (4) shows marked activity as an antioxidant (Nahas et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…The level of lipid peroxidation was asseyed by measuring thiobarbituric acid reactive substances (TBARS) [2]. GSH level was assayed in the liver homogenate prepared in phosphate buffer (pH = 7.4) using the method of Sedlak and Lindsay [16] with Ellman's reagent.…”
Section: Biochemical Assaysmentioning
confidence: 99%
“…Synthetic antioxidants have been shown to produce numerous side effects. Hence, the therapeutic use of medicinal plants in reducing free radical-induced tissue injury has been considered [1,2]. Aquilegia vulgaris (L.) (Ranunculaceae), syn.…”
Section: Introductionmentioning
confidence: 99%
“…In an early study 8 they showed significant cytotoxic action against KB cells. Anti-oxidant 15 and antihepatotoxic 16,17 properties have also been described for these compounds. Hispidulin itself has been found to have antibacterial 18 , antiedema 19 as well as plant germination and root growth inhibition activities 20 .…”
mentioning
confidence: 99%